Gamification of Mobile Banking Applications : A Systematic Literature Review - Hentati, Ahmed; Jallouli, Rim (Journal of Telecommunications and the Digital Economy, 2025)
Gamification has become a pivotal strategy for enhancing user experiences in digital platforms, particularly in mobile banking applications. The objective of this study is to investigate how gamification can improve user engagement, satisfaction, and loyalty of M-Banking users. This paper presents a systematic literature review, which was refined to 16 articles after rigorous filtering of multiple academic databases. The corpus explores various gamification elements, such as rewards, leaderboards, and challenges, through frameworks namely Technology Acceptance Model (TAM) and Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), as well as clustering methodologies. The findings demonstrate a strong positive impact of gamification on user behavior and adoption. Nevertheless, significant gaps persist, highlighting the need for further research and innovation in this area. This review provides valuable insights for banking professionals and offers directions for future research to further optimize gamified mobile banking applications.